The Influence of The Social Environment on Indonesian Migrant Workers - Damayanti, Putri; Maghfiroh, Ana; Widia Wati, Diyah Atiek; Putri, Wiffy Zalina (Indonesian Journal of Economics, Social, and Humanities, 2023)
There are many ways to carry out education in Malaysia, specifically in Selangor or at SB Sungai Buloh Kuala Lumpur, one of them is to enhance the educational system. This study intends to describe how education is implemented and carried out using a planned curriculum system that is adopted at Sungai Buloh SB Kuala Lumpur, Malaysia, to boost the effectiveness of children from migrant families. The respondents in this type of research or its design tool were student guardians and several children with migrant backgrounds, who were taken for purposive sampling and for the interview process. The instruments utilized in this type of research or its design tool were observation and interviews. Researchers have detailed the outcomes of their observations and interviews in their findings. The data gathered demonstrates that pupils from immigrant families also deserve an education on par with other students.